Anti-static wear-resistant HDPE modified plastic master batch and preparation process thereof
By using ethylene-vinyl alcohol copolymer as a pre-dispersion carrier and adding conductive fillers in stages in HDPE, combined with maleic anhydride-grafted polyethylene to improve interfacial compatibility, the problem of uneven dispersion of conductive fillers in HDPE system was solved, and the stability of antistatic properties and wear resistance were improved.
Patent Information
- Application Number
- CN202611470130.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-21
- Publication Date
- 2026-11-06
AI Technical Summary
In existing HDPE antistatic modified materials, conductive fillers are not easily dispersed uniformly in non-polar HDPE systems, which leads to increased melt processing load, decreased mechanical properties, and easy exposure and detachment of surface conductive fillers after wear, resulting in insufficient retention of antistatic properties.
Ethylene-vinyl alcohol copolymer was used as the first conductive carbon black and micron-sized flake graphite pre-dispersion carrier. Different types of conductive carbon black and graphite were added in stages, and maleic anhydride-grafted polyethylene was combined to improve interfacial compatibility. Ultra-high molecular weight polyethylene micro powder was used to improve wear resistance, and the melt mixing process was controlled in stages.
This method achieves uniform dispersion of conductive fillers in the HDPE matrix, reduces melt processing load, maintains the material's mechanical properties and antistatic properties after wear, and improves the stability of the material's wear resistance and antistatic properties.
Smart Images

Figure CN123042402A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer material modification technology, and in particular to an antistatic and wear-resistant HDPE modified plastic masterbatch and its preparation process. Background Technology
[0002] High-density polyethylene (HDPE) possesses good chemical resistance, processability, and mechanical properties, making it widely used in pipes, sheets, packaging, containers, and industrial protective products. However, HDPE is a non-polar polymer with high surface resistivity, making it prone to static electricity accumulation during friction, peeling, or transportation. For applications requiring antistatic or static dissipation properties, HDPE is typically modified by adding conductive carbon black, graphite, carbon fiber, or antistatic agents.
[0003] Conductive carbon black possesses a high degree of structure and a large specific surface area, which can reduce the surface resistivity of polymer materials; however, it is not easily uniformly dispersed in HDPE systems. Higher levels of conductive fillers tend to increase melt viscosity and extrusion load, and filler agglomeration can also affect the tensile and impact properties of the material. While simply increasing the conductive filler content can improve initial antistatic properties, it often leads to decreased processing stability and loss of mechanical properties.
[0004] In environments with frictional contact or repeated abrasion, HDPE antistatic materials need to maintain their antistatic properties after abrasion. In existing technologies, conductive fillers are often dispersed in the resin through one-time addition or simple blending. After abrasion, the distribution of the surface filler is prone to change, disrupting the contact relationship between conductive fillers and leading to increased surface resistivity. Furthermore, insufficient interfacial compatibility between HDPE and polar resins or polar fillers can also affect the stable distribution of conductive fillers in the matrix.
[0005] Therefore, there is a need to provide a modified HDPE masterbatch and its preparation process that can improve the dispersion state of conductive fillers while taking into account melt processing stability, mechanical properties, wear resistance, and the retention of antistatic properties after wear. Summary of the Invention
[0006] The technical problem solved by this invention is that in existing HDPE antistatic modified materials, conductive fillers are not easy to be uniformly dispersed and stably maintained in the non-polar HDPE system. Increasing the amount of conductive fillers can easily lead to an increase in melt processing load and a decrease in mechanical properties. At the same time, after the material is worn by friction, the surface conductive fillers are prone to exposure, detachment or changes in contact state, resulting in an increase in surface resistivity and insufficient retention of antistatic properties.
[0007] To address the above problems, the present invention provides the following technical solution: In a first aspect, the present invention provides an antistatic and wear-resistant HDPE modified plastic masterbatch, wherein the masterbatch is prepared from raw materials comprising the following parts by weight on an oven-dry basis: 35-55 parts of high-density polyethylene; 12-17 parts of ethylene-vinyl alcohol copolymer; 12-18 parts of first conductive carbon black; 2-6 parts of second conductive carbon black; 5-9 parts of micron-sized flake graphite; 8-12 parts of ultra-high molecular weight polyethylene micro powder; 4-7 parts of maleic anhydride-grafted polyethylene; Oxidized polyethylene wax 0.5 to 2 parts; 0.4 to 1 part of compound antioxidant; 0.3 to 0.8 parts of calcium stearate.
[0008] By adopting the above technical solution, the ethylene-vinyl alcohol copolymer contains hydroxyl groups and has a certain polarity, which can be used as a pre-dispersion carrier for the first conductive carbon black and some micron-sized flake graphite. The first conductive carbon black has a high oil absorption value and a high BET specific surface area, which is suitable for forming a conductive filler aggregate structure in the pre-dispersion stage; the second conductive carbon black has a relatively low oil absorption value and specific surface area, which is suitable for supplementing the contact between conductive fillers in the subsequent mixing stage. The phased use of the two types of conductive carbon black helps to reduce the problems of increased melt viscosity and increased mixing load caused by the concentrated addition of a single high-structure carbon black, and improves the distribution of conductive fillers in the HDPE matrix.
[0009] When micron-sized flake graphite is used in conjunction with conductive carbon black, the flake graphite can form surface or close-range contact areas between carbon black particles, making it easier for conductive fillers to form continuous contact relationships. Ultra-high molecular weight polyethylene (UHMWPE) micropowder distributed within the HDPE matrix can improve the material's abrasion resistance and reduce the loss of resin matrix and conductive fillers during abrasion, thereby helping to reduce the increase in surface resistivity after abrasion.
[0010] Maleic anhydride-grafted polyethylene (MPPE) is used to improve the interfacial compatibility between HDPE and ethylene-vinyl alcohol copolymers (EVOH). Under melt-blending conditions, the anhydride groups in MPPE can interact with the hydroxyl groups in the EVOH copolymer, potentially leading to esterification. The polyethylene segments in MPPE are compatible with HDPE, and the anhydride groups can participate in the EVOH phase interfacial interaction, thus reducing the interfacial differences between the HDPE and EVOH phases. This interfacial state helps maintain the dispersion of conductive carbon black and micron-sized flake graphite near the two-phase interface, reducing filler agglomeration, migration, and contact instability during processing or abrasion.
[0011] Preferably, the first conductive carbon black has an oil absorption value of 250–420 mL / 100 g and a BET specific surface area of 500–1400 m². 2 / g; the second conductive carbon black has an oil absorption value of 120-220 mL / 100g and a BET specific surface area of 60-500 m² / g. 2 / g; the oil absorption value of the first conductive carbon black is at least 60mL / 100g higher than that of the second conductive carbon black, and the volatile matter content of the first conductive carbon black is at least 0.50 percentage points higher than that of the second conductive carbon black.
[0012] By adopting the above technical solution, the first conductive carbon black is used to provide a conductive filler base with a high degree of structure, while the second conductive carbon black is used to supplement the distribution of conductive filler in the subsequent mixing stage. The differences between the two in terms of structure, specific surface area, and surface properties are beneficial for forming a more continuous conductive network while controlling the processing load.
[0013] Preferably, the viscosity-average molecular weight of the ultra-high molecular weight polyethylene micropowder is 2.0 × 10⁻⁶. 6 ~6.0×10 6 g / mol, D50 is 20-60 μm, D90 is not higher than 120 μm; the ethylene-vinyl alcohol copolymer has an ethylene structural unit content of 38-44 mol.
[0014] By adopting the above technical solutions, ultra-high molecular weight polyethylene micro powder can provide wear-resistant components in HDPE matrix, reducing mass loss during friction; ethylene-vinyl alcohol copolymer, within the above-mentioned ethylene structural unit content range, has both polarity and melt processability, making it suitable for pre-dispersion of conductive fillers.
[0015] Preferably, the micron-sized flake graphite comprises a first portion of micron-sized flake graphite and a second portion of micron-sized flake graphite, wherein the weight ratio of the first portion of micron-sized flake graphite to the second portion of micron-sized flake graphite is 1:1 to 1:2; the first portion of micron-sized flake graphite is used to prepare an EVOH-based conductive predispersant together with ethylene-vinyl alcohol copolymer, first conductive carbon black, oxidized polyethylene wax and a portion of high-density polyethylene; the second portion of micron-sized flake graphite is used to form a post-addition mixture with ultra-high molecular weight polyethylene micro powder, second conductive carbon black and calcium stearate.
[0016] By adopting the above technical solution, the first part of micron-sized flake graphite participates in pre-dispersion, which is beneficial to forming a composite dispersion structure of carbon black and graphite in the EVOH-based conductive pre-dispersion material. The second part of micron-sized flake graphite is added in a subsequent stage, which can reduce the risk of excessive breakage of flake graphite in the first stage of mixing, and make it co-distributed with the second conductive carbon black and ultra-high molecular weight polyethylene micro powder in the HDPE matrix. This staged addition method is beneficial to balance the initial antistatic properties, the retention of antistatic properties after wear, and the stability of melt processing.
[0017] Preferably, the raw materials, on an oven-dry basis, are in the following weight proportions: 40-45 parts high-density polyethylene; 13-15.5 parts ethylene-vinyl alcohol copolymer; 13.5-16.5 parts first conductive carbon black; 3.4-4.5 parts second conductive carbon black; 6.5-7.5 parts micron-sized flake graphite; 9-10.5 parts ultra-high molecular weight polyethylene powder; 5-6 parts maleic anhydride-grafted polyethylene; 1-1.5 parts oxidized polyethylene wax; 0.5-0.7 parts composite antioxidant; and 0.5-0.6 parts calcium stearate.
[0018] By adopting the above technical solution, when the content of each component is within the above range, the ratio between conductive filler, wear-resistant component, compatible component and processing aid is more suitable for preparing HDPE antistatic and wear-resistant masterbatch. This is beneficial to control the adverse effects of conductive filler on melt flow and mechanical properties while maintaining antistatic performance, and to improve the retention of antistatic performance of the material after friction and wear.
[0019] Secondly, the present invention provides a preparation process for antistatic and wear-resistant HDPE modified plastic masterbatch, which adopts the following technical solution: A process for preparing an antistatic and wear-resistant HDPE modified plastic masterbatch includes the following steps: Step 1: The ethylene-vinyl alcohol copolymer, which has been moistened with deionized water, is melt-blended with the first conductive carbon black, the first part of micron flake graphite, oxidized polyethylene wax and part of high-density polyethylene in the first extrusion stage. Then, it is subjected to vacuum dehydration, extrusion and pelletizing to obtain EVOH-based conductive predispersant. Step 2: The EVOH-based conductive pre-dispersed material, the remaining high-density polyethylene and composite antioxidant are added to the extruder for PE-g-MAH pre-mixing. After venting through the first vacuum exhaust port and establishing a melt seal, maleic anhydride grafted polyethylene is added through the side feed port for heating and compatibility treatment to obtain the compatibility-treated melt. Step 3: Cool the melt obtained in Step 2, and then add a post-addition mixture consisting of ultra-high molecular weight polyethylene micro powder, second conductive carbon black, second part of micron flake graphite and calcium stearate through the side feed port. Mix in the low shear mixing section, vent through the second vacuum exhaust port, extrude, cool and pelletize to obtain the antistatic and wear-resistant HDPE modified plastic masterbatch.
[0020] By adopting the above technical solution, the ethylene-vinyl alcohol copolymer is first adjusted for moisture content before participating in the first extrusion stage. Appropriate moisture content improves the wetting and mixing state between the ethylene-vinyl alcohol copolymer and the first conductive carbon black and the first portion of micron-sized flake graphite, making the high-structure conductive carbon black easier to disperse in the carrier containing polar groups during the pre-dispersion stage. This stage does not directly introduce all HDPE and subsequent fillers, which helps reduce the mixing load caused by adding multiple fillers at once.
[0021] After melt wetting in the first extrusion stage, vacuum dehydration is performed to remove the moisture introduced during moisture adjustment, which is then removed during the formation of the predispersant. This treatment retains the improving effect of moisture adjustment on the initial mixing stage while reducing residual moisture in the EVOH-based conductive predispersant, thus minimizing the impact of moisture on the anhydride groups when maleic anhydride-grafted polyethylene is subsequently added. Therefore, the EVOH-based conductive predispersant exhibits both good predisposition of the conductive filler and is suitable for subsequent compatibility treatment.
[0022] In the second extrusion stage, the EVOH-based conductive pre-dispersant, the remaining high-density polyethylene, and the composite antioxidant are pre-mixed before the addition of PE-g-MAH. This step allows the pre-dispersant to complete melt dispersion and preliminary mixing with the HDPE matrix, and further removes volatiles and residual moisture through the first vacuum exhaust port. Adding maleic anhydride-grafted polyethylene after the melt seal is established reduces the risk of shear loss and side reactions caused by premature entry of maleic anhydride-grafted polyethylene into the high-filler mixing zone, allowing it to participate more in the interfacial interaction between HDPE and EVOH.
[0023] After the maleic anhydride-grafted polyethylene is added, a temperature-controlled compatibility treatment is performed. This treatment allows the maleic anhydride-grafted polyethylene to come into contact with the EVOH phase within a short residence time, resulting in interfacial interactions, possibly accompanied by esterification reactions between the anhydride groups and hydroxyl groups. Since the polyethylene segments of the maleic anhydride-grafted polyethylene are compatible with HDPE, and its grafted groups can interact with the EVOH phase, this process improves the compatibility between the HDPE and EVOH phases, thereby enhancing the stability of the conductive filler distribution.
[0024] After compatibility treatment, the melt temperature is lowered before the additive mixture is added laterally. This additive mixture contains ultra-high molecular weight polyethylene (UHMWPE) micropowder, a second conductive carbon black component, a second portion of micron-sized flake graphite, and calcium stearate. Adding this component too early can increase torque and pressure fluctuations under strong shear conditions in the initial stage, and may also lead to flake graphite breakage or excessive shearing of the UHMWPE micropowder. Adding it after cooling and performing low-shear mixing helps maintain the morphology and distribution of the additive components, reduces filler agglomeration and localized overheating, and improves the retention of antistatic properties after wear.
[0025] Preferably, in step one, the ethylene-vinyl alcohol copolymer is pre-treated to adjust its moisture content: the ethylene-vinyl alcohol copolymer is dried at 80°C to reduce its moisture content to no more than 0.10% by mass, and then stirred in a closed mixer at 25°C while uniformly spraying in deionized water. The mixture is then sealed and left to stand for 6–10 hours to adjust the moisture content of the ethylene-vinyl alcohol copolymer to 0.3%–0.8% by mass; wherein the amount of deionized water used is 0.03–0.15 parts by weight.
[0026] By adopting the above technical solution, the moisture content of the ethylene-vinyl alcohol copolymer can be kept within a controllable range before entering the first extrusion stage after pre-drying. If the moisture content is too low, the wetting and mixing resistance between the first conductive carbon black and the ethylene-vinyl alcohol copolymer is large; if the moisture content is too high, the uncertainty of vacuum dehydration load and subsequent interface treatment increases. Adjusting the moisture content to 0.3%–0.8% by mass is beneficial for balancing the stability of the pre-dispersion processing in the initial stage and the requirement for low residual moisture in the subsequent stage.
[0027] Preferably, in step one, the first extrusion stage is carried out using a co-rotating twin-screw extruder with a length-to-diameter ratio of 44:1; the process parameters for vacuum dehydration are: the vacuum gauge pressure of the vacuum dehydration section is -0.095 to -0.085 MPa, and the temperature of the vacuum dehydration section is 185 to 192°C, so that the moisture content of the dehydrated EVOH-based conductive pre-dispersed material is not higher than 0.10%.
[0028] By adopting the above technical solution, vacuum dehydration is set up in the first extrusion stage after the conductive filler is wetted and dispersed, which can remove the moisture introduced in the moisture adjustment step in a timely manner. The moisture content of the dehydrated EVOH-based conductive pre-dispersed material is not higher than 0.10% by mass, which helps to reduce the impact of residual moisture in the second extrusion stage on the interfacial interaction of maleic anhydride-grafted polyethylene.
[0029] Preferably, in step two, the heating and compatibility treatment is carried out in the compatibility treatment section, the melt temperature of the compatibility treatment section is 198-208°C, and the average residence time of the material in the compatibility treatment section is 8-20s; maleic anhydride grafted polyethylene is added from the side feed port 32D downstream of the main feed port, where D represents the nominal diameter of the screw of the twin-screw extruder.
[0030] By adopting the above technical solution, maleic anhydride-grafted polyethylene is added after premixing and the first vacuum degassing, which avoids the high-filler mixing zone in the front section and allows it to enter the compatibility treatment section in a relatively stable melt state. The melt temperature of 198–208°C and the residence time of 8–20 seconds are conducive to sufficient contact between maleic anhydride-grafted polyethylene and the EVOH phase, while reducing the adverse effects of prolonged high-temperature residence on the dispersion state of the resin and conductive filler.
[0031] Preferably, in step three, before adding the post-addition mixture, the melt is passed through a cooling conveying section to reduce the melt temperature to 178-182°C; after adding the post-addition mixture, low-shear mixing is performed at 178-182°C, and the average residence time of the material is 20-45 seconds; the low-shear mixing section uses forward conveying elements and 30° kneading elements, and does not have reverse conveying elements.
[0032] By adopting the above technical solution, the post-addition mixture is added at a relatively low melt temperature and dispersed in a low-shear mixing section without reverse conveying elements. This reduces the shear damage to ultra-high molecular weight polyethylene (UHMWPE) micropowder and flake graphite, minimizing the risk of powder backflow, bridging, or localized accumulation during side feeding. This process helps maintain a relatively stable distribution of the second conductive carbon black, the second portion of micron-sized flake graphite, and UHMWPE micropowder within the HDPE matrix, thus balancing extrusion processing stability, abrasion resistance, and retention of antistatic properties after wear.
[0033] In summary, the present invention has at least one of the following beneficial technical effects: 1. This invention uses an ethylene-vinyl alcohol copolymer as a pre-dispersion carrier for the first conductive carbon black and a portion of micron-sized flake graphite. The moisture content of the ethylene-vinyl alcohol copolymer is adjusted before the first extrusion stage, allowing the first conductive carbon black and micron-sized flake graphite to be pre-dispersed in a system containing polar groups. This method helps improve the distribution of conductive fillers in the HDPE matrix and reduces the agglomeration and increased processing load problems that occur when high-structure conductive carbon black is directly added to the HDPE system.
[0034] 2. In the first extrusion stage, this invention incorporates a vacuum dehydration process to remove the moisture introduced during the moisture adjustment step after the formation of the EVOH-based conductive pre-dispersion. This results in the pre-dispersion possessing both good conductive filler dispersion and low residual moisture. This treatment helps reduce the impact of residual moisture on the maleic anhydride-grafted polyethylene interface during subsequent compatibility treatment stages, thereby improving the compatibility between the HDPE phase and the EVOH phase.
[0035] 3. In this invention, maleic anhydride-grafted polyethylene is added with a delayed addition. After the EVOH-based conductive pre-dispersant and HDPE have completed pre-mixing and undergone a first vacuum degassing, the polyethylene then enters the heating and compatibility treatment section. This process reduces the premature consumption of maleic anhydride-grafted polyethylene in the initial high-filler mixing zone, allowing it to participate more concentratedly in the interfacial interaction between HDPE and EVOH, thereby benefiting the dispersion state of the conductive filler and the maintenance of the material's mechanical properties.
[0036] 4. This invention divides micron-sized flake graphite into a first part and a second part, and, in conjunction with the staged addition of a first conductive carbon black and a second conductive carbon black, allows the conductive filler to function in both the pre-dispersion stage and the subsequent mixing stage. The first conductive carbon black and the first part of micron-sized flake graphite are used to form a pre-dispersion structure, while the second conductive carbon black and the second part of micron-sized flake graphite are used to supplement the contact relationship of subsequent conductive fillers, which is beneficial for forming a more stable conductive network and reducing processing instability caused by the concentrated addition of a single conductive filler.
[0037] 5. In this invention, after compatibility treatment, the mixture is cooled down, and then a post-addition mixture consisting of ultra-high molecular weight polyethylene micro powder, a second conductive carbon black, a second portion of micron-sized flake graphite, and calcium stearate is added. Dispersion is achieved using a low-shear mixing section. This method helps reduce excessive shear stress on the ultra-high molecular weight polyethylene micro powder and flake graphite, maintaining the distribution of wear-resistant components and conductive fillers, thereby improving the wear resistance of the masterbatch in subsequent use and the retention of antistatic properties after wear. Attached Figure Description
[0038] Figure 1 The Fourier transform infrared spectra of the compatibility-treated samples obtained in Example 1, Comparative Example 3, Comparative Example 4, and Comparative Example 5 are shown, where (a) is the spectrum of each compatibility-treated sample in the range of 4000–600 cm⁻¹. -1 Fourier transform infrared spectra within the range, (b) showing the compatibility-treated samples in the range of 1900–1650 cm⁻¹. -1 A magnified spectrum of the carbonyl absorption region within the range. Detailed Implementation
[0039] The present invention will be further described below with reference to specific embodiments. The following examples are only for illustrating the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Conventional adjustments to the raw material dosage and process parameters made by those skilled in the art without departing from the technical concept of the present invention can all be considered as embodiments of the present invention.
[0040] The specifications of the main raw materials and reagents used in the following examples and comparative examples are as follows. Polymers, fillers, and additives not specifically mentioned are all commercially available industrial-grade products, and chemical reagents not specifically mentioned are all analytical grade or higher products. Unless otherwise stated, percentages are all mass fractions, parts are all parts by mass, moisture refers to the mass fraction of moisture measured by the Karl Fischer method, and particle size refers to the volume-based particle size measured by laser diffraction.
[0041] High-density polyethylene, abbreviated as HDPE, CAS number 9002-88-4, is a homopolymer of ethylene, with repeating units of [-CH2-CH2-]. n Density is 0.945–0.960 g / cm³ 3 The melt mass flow rate is 2.0–8.0 g / 10 min (190℃, 2.16 kg), and the melting peak temperature is 125–135℃.
[0042] Ethylene-vinyl alcohol copolymer, abbreviated as EVOH, CAS number 26221-27-2, is a random copolymer formed by ethylene and vinyl alcohol structural units, with repeating units consisting of [-CH2-CH2-]. X and [-CH2-CH(OH)-] Y Composition: Ethylene structural units comprise 38–44 mol%, with a density of 1.10–1.20 g / cm³. 3 The melt mass flow rate is 1.0–8.0 g / 10 min (210℃, 2.16 kg), and the melting peak temperature is 160–178℃.
[0043] The first conductive carbon black, CAS No. 1333-86-4, has an oil absorption value (OAN) of 250–420 mL / 100 g and a BET specific surface area of 500–1400 m². 2 / g, the pH value of the aqueous dispersion is 4.0 to 8.0, the volatile matter is 1.0% to 4.0%, and the ash content is not higher than 0.50%.
[0044] The second conductive carbon black, CAS No. 1333-86-4, has an oil absorption value (OAN) of 120–220 mL / 100 g and a BET specific surface area of 60–500 m². 2 / g, the pH value of the aqueous dispersion is 7.0 to 10.5, the volatile matter is 0.20% to 1.50%, and the ash content is not higher than 0.50%. The oil absorption value of the first conductive carbon black is at least 60 mL / 100g higher than that of the second conductive carbon black, and the volatile matter of the first conductive carbon black is at least 0.50 percentage points higher than that of the second conductive carbon black.
[0045] Micron-sized flake graphite, CAS No. 7782-42-5, whose main chemical component is carbon, with a fixed carbon content of not less than 98.0%, D50 of 8-20μm, D90 of not more than 45μm, and aspect ratio of 5-40.
[0046] Ultra-high molecular weight polyethylene (UHMWPE) micropowder, abbreviated as UHMWPE micropowder, CAS number 9002-88-4, is an ethylene homopolymer with repeating units of [-CH2-CH2-]. n The viscosity-average molecular weight is 2.0 × 10⁻⁶. 6 ~6.0×10 6 g / mol, D50 is 20-60 μm, D90 is not higher than 120 μm, and loose bulk density is 0.30-0.55 g / cm³. 3 .
[0047] Maleic anhydride-grafted polyethylene, abbreviated as PE-g-MAH, is a graft polymer with polyethylene as the main chain and maleic anhydride as the grafting monomer. The repeating unit of the polyethylene main chain is [-CH2-CH2-]. n The maleic anhydride grafting rate is 0.60%–1.20%, the density is 0.91–0.96 g / cm³, the melt mass flow rate is 1.0–10.0 g / 10 min (190℃, 2.16 kg), and the melting peak temperature is 105–135℃.
[0048] Oxidized polyethylene wax, CAS No. 68441-17-8, acid value 10~35mgKOH / g, dropping point 95~120℃, melt viscosity at 140℃ 50~1000mPa·s.
[0049] Antioxidant 1010, chemically named pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid], CAS number 6683-19-8, molecular formula C 73 H 108 O 12 The purity is not less than 98.0%.
[0050] Antioxidant 168, chemical name tris(2,4-di-tert-butylphenyl) phosphite, CAS number 31570-04-4, molecular formula C 42 H 63 O3P, with a purity of not less than 98.0%. The mass ratio of antioxidant 1010 to antioxidant 168 is 1:1 to 1:3.
[0051] Calcium stearate, CAS number 1592-23-0, molecular formula Ca(C) 18 H 35 O2)2, purity not less than 98.0%, D50 is 2~15μm.
[0052] Preparation Example 1: This preparation example provides a method for preparing EVOH-based conductive predispersant P1, including the following steps: (1) Weigh 13 kg of ethylene-vinyl alcohol copolymer on an oven-dry basis. The actual weighing mass is calculated based on its initial moisture content. Dry the ethylene-vinyl alcohol copolymer at 80°C for 6 h to reduce its moisture content to 0.05%. Then add it to a closed mixer and stir at 25°C and 30 r / min. Spray 0.0326 kg of deionized water evenly over 8 min. After spraying, continue stirring for 20 min and then place it in a sealed container at 25°C for 6 h to adjust the moisture content of the ethylene-vinyl alcohol copolymer to 0.3%.
[0053] (2) Add 13.5 kg of first conductive carbon black, 2 kg of micron flake graphite and 0.8 kg of oxidized polyethylene wax to a mixer and mix at 150 r / min for 8 min to obtain powder premix.
[0054] (3) The first extrusion stage is carried out using a co-rotating twin-screw extruder with a length-to-diameter ratio of 44:1. 40% of the total mass of the moisture-adjusted ethylene-vinyl alcohol copolymer and the powder premix is added through the main feed port, the remaining 60% of the powder premix is added through the side feed port 12D downstream of the main feed port, and 12kg of high-density polyethylene is added through the side feed port 24D downstream of the main feed port.
[0055] The temperature zones of the extruder, from the feeding end to the die head, are set to 145℃, 160℃, 175℃, 185℃, 190℃, 190℃, 185℃ and 180℃ respectively. The screw speed is 280 r / min, and the total residence time of the material in the extruder is 65 to 80 seconds.
[0056] (4) After the material is melted and wetted, the first extrusion stage vacuum dehydration is carried out at 32D downstream of the main feed port. The vacuum gauge pressure is -0.085MPa, the temperature of the vacuum dehydration section is 185℃, and the average residence time of the material in the vacuum dehydration section is 15-25s, so that the moisture content of the dehydrated material is not higher than 0.10%. The dehydrated melt is extruded through a die at 180℃, air-cooled and pelletized to obtain EVOH-based conductive predispersant P1.
[0057] On an oven-dry basis, EVOH-based conductive predispersant P1 consists of 13 kg of ethylene-vinyl alcohol copolymer, 13.5 kg of first conductive carbon black, 2 kg of micron-sized flake graphite, 0.8 kg of oxidized polyethylene wax, and 12 kg of high-density polyethylene, with a total oven-dry weight of 41.3 kg.
[0058] Preparation Example 2: This preparation example provides a method for preparing EVOH-based conductive predispersant P2, including the following steps: (1) Weigh 14 kg of ethylene-vinyl alcohol copolymer on an oven-dry basis. The actual weighing mass is calculated based on its initial moisture content. Dry the ethylene-vinyl alcohol copolymer at 80°C for 6 h to reduce its moisture content to 0.05%. Then add it to a closed mixer and stir at 25°C and 35 r / min. Spray 0.0633 kg of deionized water evenly over 10 min. After spraying, continue stirring for 25 min and then place it in a sealed container at 25°C for 8 h to adjust the moisture content of the ethylene-vinyl alcohol copolymer to 0.5%.
[0059] (2) Add 14.5 kg of first conductive carbon black, 2.8 kg of micron flake graphite and 1.2 kg of oxidized polyethylene wax to a mixer and mix at 180 r / min for 10 min to obtain powder premix.
[0060] (3) The first extrusion stage is carried out using a co-rotating twin-screw extruder with a length-to-diameter ratio of 44:1. 35% of the total mass of the moisture-adjusted ethylene-vinyl alcohol copolymer and the powder premix is added through the main feed port, the remaining 65% of the powder premix is added through the side feed port 12D downstream of the main feed port, and 10 kg of high-density polyethylene is added through the side feed port 24D downstream of the main feed port.
[0061] The temperature zones of the extruder, from the feeding end to the die head, are set to 150℃, 165℃, 178℃, 188℃, 195℃, 192℃, 185℃ and 182℃ respectively. The screw speed is 330 r / min, and the total residence time of the material in the extruder is 55 to 70 seconds.
[0062] (4) After the material is melted and wetted, the first extrusion stage vacuum dehydration is carried out at 32D downstream of the main feed port. The vacuum gauge pressure is -0.090MPa, the temperature of the vacuum dehydration section is 190℃, and the average residence time of the material in the vacuum dehydration section is 15-25s, so that the moisture content of the dehydrated material is not higher than 0.08%. The dehydrated melt is extruded through a die at 182℃, air-cooled and pelletized to obtain EVOH-based conductive predispersant P2.
[0063] On an oven-dry basis, EVOH-based conductive predispersant P2 consists of 14 kg of ethylene-vinyl alcohol copolymer, 14.5 kg of first conductive carbon black, 2.8 kg of micron-sized flake graphite, 1.2 kg of oxidized polyethylene wax, and 10 kg of high-density polyethylene, with a total oven-dry weight of 42.5 kg.
[0064] Preparation Example 3: This preparation example provides a method for preparing EVOH-based conductive predispersant P3, including the following steps: (1) Weigh 15.5 kg of ethylene-vinyl alcohol copolymer on an oven-dry basis. The actual weighing mass is calculated based on its initial moisture content. Dry the ethylene-vinyl alcohol copolymer at 80°C for 6 h to reduce its moisture content to 0.05%. Then add it to a closed mixer and stir at 25°C and 40 r / min. Spray 0.1172 kg of deionized water evenly over 12 min. After spraying, continue stirring for 30 min and then place it in a sealed container at 25°C for 10 h to adjust the moisture content of the ethylene-vinyl alcohol copolymer to 0.8%.
[0065] (2) Add 16.5 kg of first conductive carbon black, 3.75 kg of micron flake graphite and 1.4 kg of oxidized polyethylene wax to a mixer and mix at 200 r / min for 12 min to obtain powder premix.
[0066] (3) The first extrusion stage is carried out using a co-rotating twin-screw extruder with a length-to-diameter ratio of 44:1. 30% of the total mass of the moisture-adjusted ethylene-vinyl alcohol copolymer and the powder premix is added through the main feed port, the remaining 70% of the powder premix is added through the side feed port 12D downstream of the main feed port, and 8 kg of high-density polyethylene is added through the side feed port 24D downstream of the main feed port.
[0067] The temperature zones of the extruder, from the feeding end to the die head, are set to 150℃, 168℃, 180℃, 190℃, 198℃, 195℃, 188℃ and 184℃ respectively. The screw speed is 380 r / min, and the total residence time of the material in the extruder is 45 to 60 seconds.
[0068] (4) After the material is melt-wetted, the first extrusion stage of vacuum dehydration is carried out at 32D downstream of the main feed port. The vacuum gauge pressure is -0.095MPa, the temperature of the vacuum dehydration section is 192℃, and the average residence time of the material in the vacuum dehydration section is 20-30s, so that the moisture content of the dehydrated material is not higher than 0.08%. The dehydrated melt is extruded through a die at 184℃, air-cooled and pelletized to obtain EVOH-based conductive predispersant P3.
[0069] On an oven-dry basis, EVOH-based conductive predispersant P3 consists of 15.5 kg of ethylene-vinyl alcohol copolymer, 16.5 kg of first conductive carbon black, 3.75 kg of micron-sized flake graphite, 1.4 kg of oxidized polyethylene wax, and 8 kg of high-density polyethylene, with a total oven-dry weight of 45.15 kg.
[0070] In the following examples, the total feed amount was 100 kg on an oven-dry basis. The EVOH-based conductive predispersants P1-P3 obtained in Examples 1-3 were dried at 75-80°C before use to ensure their moisture content did not exceed 0.05%. Their actual mass was calculated using the following formula: Actual weighed mass = oven-dry basis mass ÷ (1 - measured moisture mass fraction).
[0071] The compound antioxidant is composed of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:2.
[0072] The second extrusion stage uses a co-rotating twin-screw extruder with a length-to-diameter ratio of 56:1. A first vacuum vent is located downstream of the pre-mixing section before PE-g-MAH is added, and a melt sealing section is located downstream of the first vacuum vent. PE-g-MAH is added through a first side feed port 32D downstream of the main feed port, and the subsequent mixture is added through a second side feed port 46D downstream of the main feed port. A low-shear mixing section and a second vacuum vent are sequentially located downstream of the second side feed port.
[0073] Example 1: This example provides a preparation process for antistatic and wear-resistant HDPE modified plastic masterbatch, including the following steps: (1) Weigh out 42.5 kg of EVOH-based conductive predispersant P2 prepared in Preparation Example 2, 33.1 kg of high-density polyethylene, 5.5 kg of maleic anhydride-grafted polyethylene, 10 kg of ultra-high molecular weight polyethylene micro powder, 3.5 kg of second conductive carbon black, 4.2 kg of micron-sized flake graphite, 0.6 kg of composite antioxidant and 0.6 kg of calcium stearate, based on the amount of the dry weight.
[0074] EVOH-based conductive predispersant P2, high-density polyethylene, and composite antioxidant were added to a mixer and mixed at 120 rpm for 8 minutes to obtain the main feed mixture. Ultra-high molecular weight polyethylene powder, second conductive carbon black, micron-sized flake graphite, and calcium stearate were added to another mixer and mixed at 150 rpm for 10 minutes to obtain the post-addition mixture.
[0075] (2) The main feed mixture is added from the main feed port of the twin-screw extruder. The temperature zones of the extruder are set sequentially from the feed end to the die head as 150℃, 165℃, 180℃, 190℃, 193℃, 190℃, 198℃, 203℃, 188℃, 180℃, 180℃ and 185℃, and the screw speed is 320r / min.
[0076] (3) After the EVOH-based conductive predispersant P2 and high-density polyethylene are completely melted, the materials are mixed in the premixing section before the addition of PE-g-MAH at a melt temperature of 193℃, with an average residence time of 25s.
[0077] After premixing, venting is performed at the first vacuum vent, with a vacuum gauge pressure of -0.08 MPa and an average venting time of 10 seconds. After venting, the melt is passed through the sealed section, and maleic anhydride-grafted polyethylene is added through the first side feed port.
[0078] (4) After the maleic anhydride-grafted polyethylene is added, the material enters the compatibility treatment section with a melt temperature of 203°C and an average residence time of 12s, which promotes the interfacial interaction between maleic anhydride-grafted polyethylene and ethylene-vinyl alcohol copolymer and improves interfacial compatibility.
[0079] After the compatibility treatment is completed, the melt is passed through a 6D cooling conveyor section to reduce the melt temperature to 180℃. Once the melt temperature before the second side feed port stabilizes at 178-182℃, the post-mixture is added through the second side feed port.
[0080] (5) After the mixture is added, it is subjected to low-shear kneading at 178-182°C with an average residence time of 25s. The low-shear kneading section uses forward conveying elements and 30° kneading elements, and does not have reverse conveying elements.
[0081] The mixed material is vented at the second vacuum exhaust port with a vacuum gauge pressure of -0.075MPa. After being filtered through a 60-mesh filter, it is extruded through a die at 185℃, air-cooled and pelletized, and dried at 80℃ for 3 hours to obtain antistatic and wear-resistant HDPE modified plastic masterbatch.
[0082] The masterbatch obtained in this embodiment, on an oven-dry basis, comprises 43.1 parts of high-density polyethylene, 14 parts of ethylene-vinyl alcohol copolymer, 14.5 parts of first conductive carbon black, 3.5 parts of second conductive carbon black, 7 parts of micron-sized flake graphite, 10 parts of ultra-high molecular weight polyethylene powder, 5.5 parts of maleic anhydride-grafted polyethylene, 1.2 parts of oxidized polyethylene wax, 0.6 parts of composite antioxidant, and 0.6 parts of calcium stearate.
[0083] Example 2: This example provides a preparation process for antistatic and wear-resistant HDPE modified plastic masterbatch, including the following steps: (1) Weigh out 41.3 kg of EVOH-based conductive predispersant P1 prepared in Preparation Example 1, 38 kg of high-density polyethylene, 4.5 kg of maleic anhydride-grafted polyethylene, 8.8 kg of ultra-high molecular weight polyethylene micro powder, 3 kg of second conductive carbon black, 3.5 kg of micron-sized flake graphite, 0.5 kg of composite antioxidant and 0.4 kg of calcium stearate on an oven-dry basis.
[0084] EVOH-based conductive predispersant P1, high-density polyethylene, and composite antioxidant were mixed at 120 r / min for 8 min to obtain the main additive mixture. Ultra-high molecular weight polyethylene micro powder, second conductive carbon black, micron-sized flake graphite, and calcium stearate were mixed at 140 r / min for 8 min to obtain the post-addition mixture.
[0085] (2) The main feed mixture is added from the main feed port of the twin-screw extruder. The temperature zones of the extruder from the feed end to the die head are set to 145℃, 160℃, 175℃, 188℃, 188℃, 185℃, 192℃, 198℃, 190℃, 185℃, 183℃ and 185℃ respectively, and the screw speed is 260r / min.
[0086] (3) After the material is completely melted, it is mixed in the premixing section before the addition of PE-g-MAH at a melt temperature of 188℃, with an average residence time of 15s.
[0087] After premixing, venting is performed at the first vacuum vent, with a vacuum gauge pressure of -0.07 MPa and an average venting time of 8 seconds. After venting is completed and a melt seal is established, maleic anhydride-grafted polyethylene is added through the first side feed port.
[0088] (4) The material after adding maleic anhydride grafted polyethylene is introduced into the compatibility treatment section with a melt temperature of 198°C and the average residence time is 8s.
[0089] After the compatibility treatment is completed, the melt temperature is reduced to 185°C. Once the melt temperature before the second side feed port stabilizes at 182–185°C, the post-addition mixture is added.
[0090] (5) The material after adding the mixture was subjected to low-shear kneading at 182-185℃, with an average residence time of 20s. The kneaded material was vented at the second vacuum exhaust port, with a vacuum gauge pressure of -0.07MPa. After being filtered through a 60-mesh filter, it was extruded through a die at 185℃, air-cooled and pelletized, and dried at 75℃ for 3h to obtain antistatic and wear-resistant HDPE modified plastic masterbatch.
[0091] The masterbatch obtained in this embodiment, on an oven-dry basis, comprises 50 parts of high-density polyethylene, 13 parts of ethylene-vinyl alcohol copolymer, 13.5 parts of first conductive carbon black, 3 parts of second conductive carbon black, 5.5 parts of micron-sized flake graphite, 8.8 parts of ultra-high molecular weight polyethylene powder, 4.5 parts of maleic anhydride-grafted polyethylene, 0.8 parts of oxidized polyethylene wax, 0.5 parts of composite antioxidant, and 0.4 parts of calcium stearate.
[0092] Example 3: This example provides a preparation process for antistatic and wear-resistant HDPE modified plastic masterbatch, including the following steps: (1) Weigh out 45.15 kg of EVOH-based conductive predispersant P3 prepared in Preparation Example 3, 28.8 kg of high-density polyethylene, 6 kg of maleic anhydride grafted polyethylene, 10.5 kg of ultra-high molecular weight polyethylene micro powder, 4.5 kg of second conductive carbon black, 3.75 kg of micron-sized flake graphite, 0.7 kg of composite antioxidant and 0.6 kg of calcium stearate on an oven-dry basis.
[0093] EVOH-based conductive predispersant P3, high-density polyethylene, and composite antioxidant were mixed at 150 r / min for 10 min to obtain the main additive mixture. Ultra-high molecular weight polyethylene micro powder, second conductive carbon black, micron-sized flake graphite, and calcium stearate were mixed at 180 r / min for 12 min to obtain the post-addition mixture.
[0094] (2) The main feed mixture is added from the main feed port of the twin-screw extruder. The temperature zones of the extruder from the feed end to the die head are set to 150℃, 168℃, 182℃, 195℃, 198℃, 195℃, 202℃, 208℃, 190℃, 180℃, 178℃ and 182℃ respectively, and the screw speed is 360r / min.
[0095] (3) After the material is completely melted, it is mixed in the premixing section before the addition of PE-g-MAH at a melt temperature of 198℃, with an average residence time of 35s.
[0096] After premixing, venting is performed at the first vacuum vent, with a vacuum gauge pressure of -0.085 MPa and an average venting time of 15 seconds. After venting is completed and a melt seal is established, maleic anhydride-grafted polyethylene is added through the first side feed port.
[0097] (4) The material after maleic anhydride grafted polyethylene is introduced into the compatibility treatment section with a melt temperature of 208°C and an average residence time of 20s.
[0098] After the compatibility treatment is completed, the melt is passed through a cooling conveyor section of 8D in length to reduce the melt temperature to 178℃. After the melt temperature before the second side feed port stabilizes at 178-182℃, the post-addition mixture is added.
[0099] (5) The material after the addition of the mixture was subjected to low-shear kneading at 178-182℃, with an average residence time of 45s. The kneaded material was vented at the second vacuum exhaust port with a vacuum gauge pressure of -0.085MPa. After being filtered through a combination of 40-mesh and 60-mesh filters, it was extruded through a die at 182℃, air-cooled and pelletized, and dried at 80℃ for 4h to obtain antistatic and wear-resistant HDPE modified plastic masterbatch.
[0100] The masterbatch obtained in this embodiment, on an oven-dry basis, comprises 36.8 parts of high-density polyethylene, 15.5 parts of ethylene-vinyl alcohol copolymer, 16.5 parts of first conductive carbon black, 4.5 parts of second conductive carbon black, 7.5 parts of micron-sized flake graphite, 10.5 parts of ultra-high molecular weight polyethylene powder, 6 parts of maleic anhydride-grafted polyethylene, 1.4 parts of oxidized polyethylene wax, 0.7 parts of composite antioxidant, and 0.6 parts of calcium stearate.
[0101] Example 4: This example provides a preparation process for antistatic and wear-resistant HDPE modified plastic masterbatch, including the following steps: (1) Weigh out 41.3 kg of EVOH-based conductive predispersant P1 prepared in Preparation Example 1, 35 kg of high-density polyethylene, 5 kg of maleic anhydride grafted polyethylene, 9.5 kg of ultra-high molecular weight polyethylene micro powder, 4.5 kg of second conductive carbon black, 3.7 kg of micron-sized flake graphite, 0.5 kg of composite antioxidant and 0.5 kg of calcium stearate on an oven-dry basis.
[0102] EVOH-based conductive predispersant P1, high-density polyethylene, and composite antioxidant were mixed at 130 r / min for 8 min to obtain the main additive mixture. Ultra-high molecular weight polyethylene micro powder, second conductive carbon black, micron-sized flake graphite, and calcium stearate were mixed at 150 r / min for 10 min to obtain the post-addition mixture.
[0103] (2) The main feed mixture is added from the main feed port of the twin-screw extruder. The temperature zones of the extruder from the feed end to the die head are set to 148℃, 163℃, 178℃, 190℃, 192℃, 190℃, 197℃, 202℃, 188℃, 180℃, 180℃ and 184℃ respectively, and the screw speed is 310r / min.
[0104] (3) After the material is completely melted, it is mixed in the premixing section before the addition of PE-g-MAH at a melt temperature of 192℃, with an average residence time of 22s.
[0105] After premixing, venting is performed at the first vacuum vent, with a vacuum gauge pressure of -0.075 MPa and an average venting time of 10 seconds. After venting is completed and a melt seal is established, maleic anhydride-grafted polyethylene is added through the first side feed port.
[0106] (4) The material after adding maleic anhydride grafted polyethylene is introduced into the compatibility treatment section with a melt temperature of 202°C and the average residence time is 14s.
[0107] After the compatibility treatment is completed, the melt temperature is reduced to 180°C. Once the melt temperature before the second side feed port stabilizes at 178–182°C, the post-addition mixture is added.
[0108] (5) The material after the addition of the mixture was subjected to low-shear kneading at 178-182℃, with an average residence time of 28s. The kneaded material was vented at the second vacuum exhaust port with a vacuum gauge pressure of -0.075MPa. After being filtered through a 60-mesh filter, it was extruded through a die at 184℃, air-cooled and pelletized, and dried at 80℃ for 3h to obtain antistatic and wear-resistant HDPE modified plastic masterbatch.
[0109] The masterbatch obtained in this embodiment, on an oven-dry basis, comprises 47 parts of high-density polyethylene, 13 parts of ethylene-vinyl alcohol copolymer, 13.5 parts of first conductive carbon black, 4.5 parts of second conductive carbon black, 5.7 parts of micron-sized flake graphite, 9.5 parts of ultra-high molecular weight polyethylene powder, 5 parts of maleic anhydride-grafted polyethylene, 0.8 parts of oxidized polyethylene wax, 0.5 parts of composite antioxidant, and 0.5 parts of calcium stearate.
[0110] Example 5: This example provides a preparation process for antistatic and wear-resistant HDPE modified plastic masterbatch, including the following steps: (1) Weigh out 45.15 kg of EVOH-based conductive predispersant P3 prepared in Preparation Example 3, 32.1 kg of high-density polyethylene, 5.5 kg of maleic anhydride grafted polyethylene, 9 kg of ultra-high molecular weight polyethylene micro powder, 3.4 kg of second conductive carbon black, 3.75 kg of micron-sized flake graphite, 0.6 kg of composite antioxidant and 0.5 kg of calcium stearate on an oven-dry basis.
[0111] EVOH-based conductive predispersant P3, high-density polyethylene, and composite antioxidant were mixed at 140 r / min for 10 min to obtain the main additive mixture. Ultra-high molecular weight polyethylene micro powder, second conductive carbon black, micron-sized flake graphite, and calcium stearate were mixed at 170 r / min for 10 min to obtain the post-addition mixture.
[0112] (2) The main feed mixture is added from the main feed port of the twin-screw extruder. The temperature zones of the extruder from the feed end to the die head are set to 150℃, 165℃, 180℃, 192℃, 195℃, 192℃, 199℃, 204℃, 188℃, 180℃, 178℃ and 184℃ respectively, and the screw speed is 340r / min.
[0113] (3) After the material is completely melted, it is mixed in the premixing section before the addition of PE-g-MAH at a melt temperature of 195℃, with an average residence time of 28s.
[0114] After premixing, venting is performed at the first vacuum vent, with a vacuum gauge pressure of -0.08 MPa and an average venting time of 12 seconds. After venting is completed and a melt seal is established, maleic anhydride-grafted polyethylene is added through the first side feed port.
[0115] (4) The material after adding maleic anhydride grafted polyethylene is introduced into the compatibility treatment section with a melt temperature of 204°C and the average residence time is 15s.
[0116] After the compatibility treatment is completed, the melt temperature is reduced to 178°C. Once the melt temperature before the second side feed port stabilizes at 178–182°C, the post-addition mixture is added.
[0117] (5) The material after the addition of the mixture was subjected to low-shear kneading at 178-182℃, with an average residence time of 30s. The kneaded material was vented at the second vacuum exhaust port with a vacuum gauge pressure of -0.08MPa. After being filtered through a 60-mesh filter, it was extruded through a die at 184℃, air-cooled and pelletized, and dried at 80℃ for 3h to obtain antistatic and wear-resistant HDPE modified plastic masterbatch.
[0118] The masterbatch obtained in this embodiment, on an oven-dry basis, comprises 40.1 parts of high-density polyethylene, 15.5 parts of ethylene-vinyl alcohol copolymer, 16.5 parts of first conductive carbon black, 3.4 parts of second conductive carbon black, 7.5 parts of micron-sized flake graphite, 9 parts of ultra-high molecular weight polyethylene powder, 5.5 parts of maleic anhydride-grafted polyethylene, 1.4 parts of oxidized polyethylene wax, 0.6 parts of composite antioxidant, and 0.5 parts of calcium stearate.
[0119] Example 6: This example provides a preparation process for antistatic and wear-resistant HDPE modified plastic masterbatch, including the following steps: (1) Weigh out 42.5 kg of EVOH-based conductive predispersant P2 prepared in Preparation Example 2, 34 kg of high-density polyethylene, 5.8 kg of maleic anhydride-grafted polyethylene, 9 kg of ultra-high molecular weight polyethylene micro powder, 3.8 kg of second conductive carbon black, 3.7 kg of micron-sized flake graphite, 0.6 kg of composite antioxidant and 0.6 kg of calcium stearate, based on the dry basis.
[0120] EVOH-based conductive predispersant P2, high-density polyethylene, and composite antioxidant were mixed at 130 r / min for 8 min to obtain the main additive mixture. Ultra-high molecular weight polyethylene micro powder, second conductive carbon black, micron-sized flake graphite, and calcium stearate were mixed at 160 r / min for 10 min to obtain the post-addition mixture.
[0121] (2) The main feed mixture is added from the main feed port of the twin-screw extruder. The temperature zones of the extruder from the feed end to the die head are set to 150℃, 165℃, 180℃, 188℃, 188℃, 186℃, 200℃, 208℃, 190℃, 180℃, 178℃ and 182℃ respectively, and the screw speed is 300r / min.
[0122] (3) After the material is completely melted, it is mixed in the premixing section before the addition of PE-g-MAH at a melt temperature of 188℃, with an average residence time of 15s.
[0123] After premixing, venting is performed at the first vacuum vent, with a vacuum gauge pressure of -0.08 MPa and an average venting time of 8 seconds. After venting is completed and a melt seal is established, maleic anhydride-grafted polyethylene is added through the first side feed port.
[0124] (4) The material after adding maleic anhydride grafted polyethylene is introduced into the compatibility treatment section with a melt temperature of 208°C and the average residence time is 8s.
[0125] After the compatibility treatment is completed, the melt temperature is reduced to 178°C. Once the melt temperature before the second side feed port stabilizes at 178–182°C, the post-addition mixture is added.
[0126] (5) The material after adding the mixture was subjected to low-shear kneading at 178-182℃, with an average residence time of 20s. The kneaded material was vented at the second vacuum exhaust port with a vacuum gauge pressure of -0.08MPa. After being filtered through a 60-mesh filter, it was extruded through a die at 182℃, air-cooled and pelletized, and dried at 80℃ for 3h to obtain antistatic and wear-resistant HDPE modified plastic masterbatch.
[0127] The masterbatch obtained in this embodiment, on an oven-dry basis, comprises 44 parts of high-density polyethylene, 14 parts of ethylene-vinyl alcohol copolymer, 14.5 parts of first conductive carbon black, 3.8 parts of second conductive carbon black, 6.5 parts of micron-sized flake graphite, 9 parts of ultra-high molecular weight polyethylene powder, 5.8 parts of maleic anhydride-grafted polyethylene, 1.2 parts of oxidized polyethylene wax, 0.6 parts of composite antioxidant, and 0.6 parts of calcium stearate.
[0128] Comparative Example 1: The difference between this comparative example and Example 1 is that: EVOH-based conductive pre-dispersion P2, high-density polyethylene, maleic anhydride-grafted polyethylene, ultra-high molecular weight polyethylene micro powder, second conductive carbon black, micron-sized flake graphite, composite antioxidant, and calcium stearate are all added at once through the main feed port of the twin-screw extruder. Pre-mixing before adding PE-g-MAH is not performed, and the delayed addition of PE-g-MAH and the side-feeding process for the post-addition mixture are not used. Apart from the above differences, the remaining raw material composition and process conditions are the same as in Example 1.
[0129] Comparative Example 2: The difference between this comparative example and Example 1 is that, in preparing the EVOH-based conductive pre-dispersion P2, the EVOH was pre-dried without moisture adjustment, and the moisture content of the EVOH before entering the first extrusion stage was no higher than 0.1%. Apart from the above differences, the other raw material composition and process conditions are the same as in Example 1.
[0130] Comparative Example 3: The difference between this comparative example and Example 1 is that, in preparing the EVOH-based conductive predispersant P2, the EVOH was predisposed to conductive filler after moisture adjustment, but vacuum dehydration in the first extrusion stage was not performed. The resulting EVOH-based conductive predispersant P2 was directly used in the second extrusion stage. Apart from the above differences, the remaining raw material composition and process conditions are the same as in Example 1.
[0131] Comparative Example 4: The difference between this comparative example and Example 1 is that maleic anhydride-grafted polyethylene, EVOH-based conductive pre-dispersion material P2, high-density polyethylene, and composite antioxidant are all added from the main feed port. Pre-mixing before adding PE-g-MAH is not performed, nor is the delayed addition process of PE-g-MAH used. Apart from the above differences, the remaining raw material composition and process conditions are the same as in Example 1.
[0132] Comparative Example 5: The difference between this comparative example and Example 1 is that, after the maleic anhydride-grafted polyethylene is added through the first side feed port, a short-term heating and compatibility treatment section at 203°C is not set up. Instead, the mixing continues at 193°C, with an average residence time of 12 seconds. Apart from the above differences, the other raw material composition and process conditions are the same as in Example 1.
[0133] Comparative Example 6: The difference between this comparative example and Example 1 is that, after maleic anhydride-grafted polyethylene was added and subjected to compatibility treatment at 203°C, it was added directly to the mixture at 203°C without cooling, and then kneaded at 203°C for 25 seconds. Apart from the above differences, the remaining raw material composition and process conditions are the same as in Example 1.
[0134] Comparative Example 7: The difference between this comparative example and Example 1 is that: ultra-high molecular weight polyethylene micro powder, second conductive carbon black, post-added micron-sized flake graphite and calcium stearate, along with EVOH-based conductive pre-dispersion material P2, high-density polyethylene and composite antioxidant, are added together from the main feed port, and the cooling-after-side feeding and low-shear mixing process are not used. Apart from the above differences, the remaining raw material composition and process conditions are the same as in Example 1.
[0135] Comparative Example 8: The difference between this comparative example and Example 1 is that ultra-high molecular weight polyethylene (UHMWPE) micropowder is not added, and it is replaced with an equal mass of high-density polyethylene (HDPE), that is, the total amount of HDPE is adjusted from 43.1 parts to 53.1 parts. Apart from the above differences, the remaining raw material composition and process conditions are the same as in Example 1.
[0136] Comparative Example 9: This comparative example prepared a comparative EVOH-based conductive predispersant according to the EVOH moisture adjustment method and the first extrusion stage process of Preparation Example 2, including the following steps: (1) Compared with Preparation Example 2, the amount of first conductive carbon black was adjusted from 14.5 kg to 18 kg, and the amounts of ethylene-vinyl alcohol copolymer, micron flake graphite, oxidized polyethylene wax and high-density polyethylene were kept at 14 kg, 2.8 kg, 1.2 kg and 10 kg, respectively.
[0137] A powder premix consisting of first conductive carbon black, micron-sized flake graphite, and oxidized polyethylene wax was added from the main feed port and a side feed port 12D downstream of the main feed port, respectively, at mass ratios of 35% and 65% as specified in Preparation Example 2. The total oven-dry weight of the resulting comparative EVOH-based conductive premix was 46 kg.
[0138] (2) In the second extrusion stage, on an oven-dry basis, weigh 46 kg of the above-mentioned comparative EVOH-based conductive predispersant, 33.1 kg of high-density polyethylene, 5.5 kg of maleic anhydride-grafted polyethylene, 10 kg of ultra-high molecular weight polyethylene micro powder, 4.2 kg of micron-sized flake graphite, 0.6 kg of composite antioxidant, and 0.6 kg of calcium stearate, without adding the second conductive carbon black. Except for the above differences, the process conditions for the second extrusion stage are the same as in Example 1.
[0139] Comparative Example 10: This comparative example prepared a comparative EVOH-based conductive predispersant according to the EVOH moisture adjustment method and the first extrusion stage process of Preparation Example 2, including the following steps: (1) Compared with Preparation Example 2, the amount of micron-sized flake graphite was adjusted from 2.8 kg to 7 kg, and the amounts of ethylene-vinyl alcohol copolymer, first conductive carbon black, oxidized polyethylene wax and high-density polyethylene were kept at 14 kg, 14.5 kg, 1.2 kg and 10 kg, respectively.
[0140] A powder premix consisting of conductive carbon black, micron-sized flake graphite, and oxidized polyethylene wax was added from the main feed port and a side feed port 12D downstream of the main feed port, respectively, at mass ratios of 35% and 65% as specified in Preparation Example 2. The total oven-dry weight of the resulting comparative EVOH-based conductive premix was 46.7 kg.
[0141] (2) In the second extrusion stage, weigh 46.7 kg of the above-mentioned comparative EVOH-based conductive pre-dispersion material, 33.1 kg of high-density polyethylene, 5.5 kg of maleic anhydride-grafted polyethylene, 10 kg of ultra-high molecular weight polyethylene micro powder, 3.5 kg of second conductive carbon black, 0.6 kg of composite antioxidant, and 0.6 kg of calcium stearate on an oven-dry basis. Micron-sized flake graphite is no longer added to the second side feed port. Except for the above differences, the process conditions for the second extrusion stage are the same as in Example 1.
[0142] Test Example 1: The testing steps are as follows: (1) The polar conductive predispersants P1 to P3 obtained in Preparation Examples 1 to 3, the unconditioned polar conductive predispersant obtained in Comparative Example 2, and the polar conductive predispersant obtained in Comparative Example 3 without intermediate vacuum dehydration were used as test objects. Three batches of independent tests were conducted in each group. Samples were taken and data were recorded after the extruder was running stably.
[0143] (2) Samples of EVOH after basic drying and samples before entering the first extrusion process were collected respectively. EVOH after conditioning and sealing for Preparation Examples 1-3 was collected, dried EVOH without conditioning was collected for Comparative Example 2, and EVOH after conditioning according to Preparation Example 2 was collected for Comparative Example 3. Samples were taken from the top, middle and bottom of the material respectively, mixed and sealed for storage.
[0144] (3) After the first extrusion process stabilizes, a melt sample before dehydration is collected upstream of the vacuum dehydration section. For Preparation Examples 1-3 and Comparative Example 2, the final sample is collected at the die after vacuum dehydration; for Comparative Example 3, the sample is collected at the same location without turning on the vacuum exhaust. Samples are taken at each sampling point once every 5 minutes, for a total of 3 times. The samples are sealed and stored after cooling.
[0145] (4) Moisture content was determined using a coulometric Karl Fischer moisture analyzer with a headspace heater. 1.0 g of EVOH sample was taken, and the heater temperature was 160℃; 0.5 g of polar conductive pre-dispersed material sample was taken, and the heater temperature was 180℃; the nitrogen flow rate was 50 mL / min. Each sample was measured in triplicate, and the testing principle was in accordance with ISO 15512:2019.
[0146] (5) A condensation collection device is installed between the vacuum exhaust port and the vacuum pump. The mass of the condensation collection bottle is weighed before and after the test, and the mass of the condensate generated during no-load operation is subtracted to obtain the mass of the vacuum condensate. In Comparative Example 3, the vacuum exhaust was not turned on, and this data was not recorded.
[0147] (6) After the first extruder has been running stably for 10 minutes, the main torque and die head pressure are continuously recorded at a frequency of 1 Hz within 20 minutes through the equipment control system, and the average torque, torque standard deviation, average die head pressure and die head pressure standard deviation are calculated.
[0148] (7) Dry the final polar conductive predispersed material of each group at 80°C until the moisture content is not higher than 0.05%. Measure the melt mass flow rate at 190°C and 5.0 kg. The preheating time is 6 min. Take 5 segments of extrudate from each sample. The test principle is in accordance with ISO 1133-1:2022.
[0149] (8) The intermediate dehydration rate is calculated according to the following formula: Intermediate dehydration rate = (moisture content before vacuum dehydration - final moisture content) ÷ moisture content before vacuum dehydration × 100%.
[0150] The test results are shown in Tables 1 and 2.
[0151] Table 1. Results of controlled moisture content and intermediate dehydration tests: ; Table 2. Test results of processing performance in the first extrusion process: ; According to Tables 1 and 2, the moisture content of EVOH in Preparation Examples 1-3 before entering the first extrusion process was 0.303%, 0.497%, and 0.793%, respectively. After intermediate vacuum dehydration, the moisture content of the polar conductive predispersant decreased to 0.043%, 0.038%, and 0.047%, respectively. As the moisture content increased during conditioning, the mass of the vacuum condensate increased accordingly, indicating that the moisture introduced during conditioning could be removed during the first extrusion process.
[0152] Compared to Preparation Example 2, Comparative Example 2, which did not undergo controlled humidity conditioning, showed an increase in average torque from 56.3% to 74.8%, an increase in average die pressure from 7.82 MPa to 11.16 MPa, and a decrease in melt mass flow rate from 1.11 g / 10 min to 0.52 g / 10 min. The results indicate that controlled humidity conditioning is beneficial for reducing the mixing load in the first extrusion process and improving the melt flow state of the polar conductive predispersant.
[0153] The average torque of Preparation Example 3 was lower than that of Preparation Examples 1 and 2, but the torque fluctuation, head pressure fluctuation and condensate quality all increased, indicating that higher moisture content would increase the vacuum dehydration load and processing fluctuation.
[0154] Comparative Example 3 did not undergo intermediate vacuum dehydration, and its final moisture content was 0.153%, which was higher than that of Preparation Example 2 (0.038%). The moisture content and front-end processing parameters of the two examples before vacuum dehydration were similar, indicating that the difference in final moisture content was mainly caused by the intermediate vacuum dehydration step.
[0155] The above results indicate that controlled EVOH humidity conditioning is beneficial to improving the mixing state in the first extrusion stage, and intermediate vacuum dehydration can reduce the residual moisture of the pre-dispersed material. The combination of the two is beneficial to balance the stability of pre-dispersed processing and the moisture conditions required for subsequent compatibility treatment.
[0156] Test Example 2: The testing steps are as follows: (1) The masterbatches obtained in Examples 1, 3, 4 and 5 were used as test objects. During the second extrusion process of each group, compatibility-treated samples were collected at the axial position corresponding to the outlet of the compatibility reaction section in Example 1, before the addition of the wear-resistant conductive mixture. The compatibility-treated samples were used for Fourier transform infrared spectroscopy and residual anhydride group content testing. The final masterbatch was used for differential scanning calorimetry, dynamic rheology and melt mass flow rate testing. Three batches of independent tests were conducted in each group, and samples were taken after the extrusion state stabilized for 10 minutes.
[0157] (2) The compatibility-treated sample and the final masterbatch were vacuum dried at 80°C for 4 hours and then cooled to room temperature in a desiccator. The compatibility-treated sample was chopped and used for infrared spectroscopy and solvent extraction tests.
[0158] (3) The compatibility-treated samples were measured using an attenuated total reflectance Fourier transform infrared spectrometer with a scanning range of 4000–600 cm⁻¹. -1 The resolution is 4cm. -1 The number of scans was 32. Baseline correction was performed on the spectrum, and the result was measured at 1463 cm⁻¹. -1 The polyethylene methylene bending vibration peak was used as the normalization reference. Recorded at 1860 cm⁻¹. -1 and 1780cm -1 Nearby carbonyl absorption of acid anhydrides, 1735 cm⁻¹ -1 Nearby ester carbonyl absorption and 1712 cm -1 The carbonyl group of the nearby carboxylic acid absorbs the substance.
[0159] The relative indices of anhydride groups, ester groups, and carboxyl groups are calculated according to the following formulas: Relative index of anhydride groups I a = (A 1860 +A 1780 )÷A 1463 ; Ester group relative index I e =A 1735 ÷A 1463 ; Carboxyl relative index I c =A 1712 ÷A 1463 .
[0160] Background correction was performed on the carbonyl absorption generated by oxidized polyethylene wax and the resin itself using a blank sample with the same composition as in Example 1, but with the same mass of high-density polyethylene instead of PE-g-MAH.
[0161] (4) Weigh 10.00 g of the compatibility-treated sample, add 250 mL of xylene, reflux at 135 °C for 4 h, and filter while hot. Add 5 times its volume of acetone to the filtrate to precipitate the polymer, and vacuum dry the precipitate at 60 °C to constant weight. Prepare calibration samples using PE-g-MAH and HDPE with known maleic anhydride grafting rates, determine the relative index of anhydride groups using the same method, and establish a calibration relationship. Calculate the residual anhydride group content in the extractable phase based on this. This index is used for relative comparison between different test objects.
[0162] (5) The final masterbatch was tested using a differential scanning calorimeter, following the principles of ISO 11357-1 and ISO 11357-3. 6–8 mg of sample was weighed and heated from 25 °C to 220 °C at a rate of 10 °C / min under a nitrogen atmosphere, held for 3 min; then cooled to 40 °C at a rate of 10 °C / min, followed by a second heating to 220 °C at the same rate. The melting peak temperature of HDPE, the melting peak temperature of EVOH, the crystallization peak temperature of HDPE, and the total enthalpy of fusion during the second heating were recorded.
[0163] (6) The dynamic rheological properties of the final masterbatch were determined using a parallel plate rotational rheometer, with testing principles following ISO 6721-10. The sample was pressed into a disc with a diameter of 25 mm and a thickness of 1.2 mm at 200 °C. The test temperature was 200 °C, the diameter of the parallel plate was 25 mm, and the test gap was 1.0 mm. After determining the linear viscoelastic region by strain scanning, frequency scanning was performed within the range of 0.5% strain and 0.1–100 rad / s angular frequency. The storage modulus G', loss modulus G”, and complex viscosity η* were recorded.
[0164] (7) The melt flow rate of the final masterbatch was determined by mass method. The test conditions were 190℃, 5.0 kg, and a preheating time of 6 min. Five segments of extrudate were continuously cut from each sample. Each test was performed in triplicate, and the results are expressed as mean ± standard deviation.
[0165] The test results are shown in Tables 3 to 5 and Figure 1 .
[0166] Table 3. Infrared spectra and residual anhydride group test results of each group of compatibility-treated samples: ; Table 4. Differential scanning calorimetry results of the final masterbatch for each group: ; Table 5. Dynamic rheological and melt mass flow rate test results of the final masterbatch for each group: ; According to Tables 3 to 5 and Figure 1 In Example 1, the relative index of anhydride groups and the content of extractable residual anhydride groups were lower than those in Comparative Examples 4 and 5, while the relative index of ester groups was higher than that in Comparative Examples 3-5. The decrease in anhydride groups was accompanied by an increase in ester-related absorption, which is consistent with the result that some anhydride groups in PE-g-MAH participate in the interfacial compatibility of EVOH.
[0167] Comparative Example 3, which did not undergo intermediate vacuum dehydration, had a carboxyl group relative index of 0.186, higher than 0.091 in Example 1, while the ester group relative index decreased to 0.121. The reduction in anhydride groups was mainly accompanied by enhanced carboxyl-related absorption, which may be related to anhydride group hydrolysis or interfacial state changes caused by the higher water content conditions in the early stage. Since vacuum degassing was still set during the second extrusion process before the addition of PE-g-MAH, the test results are not used to directly determine the actual moisture content of the melt at the time of PE-g-MAH addition.
[0168] Comparative Example 4, with PE-g-MAH added beforehand, and Comparative Example 5, without a short-term heating compatibility section, had residual anhydride group contents of 2.84 mmol / kg and 3.31 mmol / kg, respectively, both higher than in Example 1; their relative ester group indices were 0.157 and 0.143, respectively, both lower than in Example 1. These results indicate that pre-mixing without a compatibilizer before adding PE-g-MAH and performing a short-term heating treatment is beneficial for improving the utilization of anhydride groups at the interface.
[0169] In Example 1, the total enthalpy of melting during the second heating was lower than that of Comparative Examples 3-5, and its low-frequency storage modulus and complex viscosity were higher, while the melt mass flow rate was lower. These changes are consistent with the state in Example 1 where the polymer segments were subject to strong interfacial constraints.
[0170] Combine Tables 3 to 5 and Figure 1 The test results show that there is a process correlation between intermediate dehydration, delayed addition of PE-g-MAH, and short-time heating compatibility treatment, which corresponds to the trend that the anhydride groups are fully utilized at the HDPE / EVOH interface.
[0171] Test Example 3: The testing steps are as follows: (1) The second extrusion processes of Examples 1-6, Comparative Examples 1, 4, 6, and 7 were used as test objects. Each group used the same twin-screw extruder, with consistent screw combinations, die settings, and sensor configurations, and operated according to the processes specified in the corresponding examples or comparative examples. To ensure the comparability of filtration pressure differences, all groups in Test Example 3 used a 60-mesh filter; the 40-mesh and 60-mesh combined filter used in the original preparation process of Example 3 was not used in this test example. The total feed rate was set to 25 kg / h, and each group conducted 3 independent batches of tests, with each batch running continuously for 180 minutes.
[0172] (2) After the feed rate, screw speed, melt temperature, and die head pressure have stabilized for 15 minutes, continuously record the main engine torque, main drive power, and die head pressure at a frequency of 1 Hz for 60 minutes. The main engine torque is expressed as the percentage of the actual torque to the rated torque, and the main drive energy consumption per unit mass is calculated according to the following formula: Energy consumption per unit mass of main drive = Main drive power during stable operation ÷ Actual feed rate.
[0173] The unit for main drive power is kW, the unit for actual feed rate is kg / h, and the unit for main drive energy consumption per unit mass is kWh / kg.
[0174] (3) Melt pressure sensors are installed at the inlet and outlet of the filter screen. The pressure at the die head is taken as the pressure at the inlet of the filter screen, and the pressure difference across the filter screen is the difference between the inlet pressure and the outlet pressure. A new 60-mesh filter screen is replaced before the start of each batch of tests. The melt temperature at the die head connection section is measured using an insertion thermocouple, and is recorded every 10 seconds for 60 minutes.
[0175] (4) For Examples 1-6, Comparative Examples 4 and 6, the instantaneous mass flow rate of the post-abrasion-resistant conductive mixture was recorded using a loss-in-weight side feeder for 20 minutes at a frequency of 1 Hz. The coefficient of variation of the side feed mass flow rate was calculated according to the following formula: The coefficient of variation of the mass flow rate of side feed = standard deviation of instantaneous mass flow rate ÷ average mass flow rate × 100%.
[0176] Comparative Examples 1 and 7 did not use the post-side feeding process, so this indicator was not calculated.
[0177] (5) Record the number of times torque alarms, abnormal pressure fluctuations at the die head, extruder breakage, and manual feed adjustment occur during continuous operation. A torque alarm is recorded when the torque is higher than 90% of the rated torque of the equipment for 5 consecutive seconds; an abnormal pressure fluctuation is recorded when the die head pressure deviates from the average value of the previous 5 minutes by more than 15% and lasts for more than 10 seconds; and a manual feed adjustment is recorded when manual handling is required due to feed bridging, backflow, or flow deviation exceeding the set value by more than 10%.
[0178] (6) The effective continuous running time is 180 min minus the actual running time after shutdown for cleaning, filter replacement, re-pulling of the bar and interruption of feeding.
[0179] (7) The masterbatch obtained from each group was dried at 80℃ for 4 hours, and the melt mass flow rate was measured at 190℃ and 5.0 kg. The preheating time was 6 min, and 5 segments of extrudate were continuously cut from each sample. The processing parameters and melt mass flow rate are expressed as the average value ± standard deviation of 3 batches of tests. The number of abnormalities and the effective continuous running time are the average value of 3 batches of tests.
[0180] The test results are shown in Tables 6 and 7.
[0181] Table 6. Test results of processing parameters for the second extrusion process: ; Note: Comparative Examples 1 and 7 did not use the post-feeding process of wear-resistant conductive mixture, and the coefficient of variation of mass flow rate of the side feed material is not applicable.
[0182] Table 7 Results of continuous operation stability test for the second extrusion process: ; According to Tables 6 and 7, the average torque of Examples 1-6 accounts for 56.8% to 72.9% of the rated torque, the main drive energy consumption per unit mass is 0.301 to 0.418 kWh / kg, the pressure difference across the filter screen is 0.39 to 0.82 MPa, and the effective continuous operating time is 175.8 to 180.0 min. Examples 3 and 5 have higher filler content, resulting in increased torque, main drive energy consumption per unit mass, and filter screen pressure difference, but they can still complete continuous extrusion.
[0183] Compared with Example 1, Comparative Example 1 added all raw materials at once, and its average torque, main drive energy consumption per unit mass and head pressure increased to 86.5%, 0.543 kWh / kg and 17.92 MPa, respectively. The pressure difference before and after the filter screen increased to 1.34 MPa, and the effective continuous running time decreased to 132.6 min. This indicates that adding all raw materials at once will increase the load on the front-end mixing and conveying.
[0184] Comparative Example 4, with the addition of PE-g-MAH in advance, exhibited higher average torque, main drive energy consumption per unit mass, head pressure, and filter pressure differential than Example 1, with an effective continuous operating time of 160.8 min. Pre-mixing without compatibilizers before adding PE-g-MAH facilitates the phased implementation of conductive pre-dispersion and compatibility treatment.
[0185] Comparative Example 6, which was not cooled after compatibility treatment, had lower average torque and die head pressure than Example 1, but its actual melt temperature was 201.8°C, the coefficient of variation of the side feed mass flow rate increased to 5.7%, the number of manual feed adjustments was 4.3, and the effective continuous running time decreased to 151.5 min. These results indicate that lower instantaneous flow resistance did not correspondingly improve the side feeding stability of the post-powder.
[0186] Comparative Example 7 showed that when UHMWPE micro powder and post-conductive filler were added from the main feed port in advance, the average torque was 81.2%, the pressure difference before and after the filter screen was 1.18 MPa, and the effective continuous operating time was 141.9 min. Adding the post-wear-resistant conductive component in advance increases the load on the front-end solid material and the fluctuation in conveying speed.
[0187] The above results indicate that premixing without compatibilizer, delayed addition of PE-g-MAH, cooling after compatibilization treatment, and post-addition of the wear-resistant and conductive mixture with low shear correspond to lower processing load, smaller pressure fluctuations, and longer effective continuous operating time.
[0188] Test Example 4: The testing steps are as follows: (1) The masterbatches obtained in Examples 1-6 and Comparative Examples 1-10 were used as test objects. Each group of masterbatches was mixed with HDPE of the same specification at a mass ratio of 20:80. After drying at 80°C for 4 hours, flat samples with dimensions of 100mm×100mm×2mm were prepared using the same injection molding machine. The barrel temperature from the feeding section to the nozzle was 175°C, 185°C, 195°C and 205°C respectively, the mold temperature was 50°C, the injection pressure was 75MPa, the holding pressure was 45MPa, the holding time was 10s and the cooling time was 25s.
[0189] (2) Each group of samples was divided into two groups of 5 pieces each, and conditioned for 48 hours in environments of 23℃ and 50% relative humidity and 23℃ and 12% relative humidity, respectively. Ten independent samples were used for each humidity condition, of which 5 pieces were used for surface resistivity and volume resistivity testing, and the other 5 pieces were used for electrostatic decay time testing.
[0190] (3) The surface resistivity was determined using a concentric circular electrode with a protective ring. The diameter of the central measuring electrode was 50 mm, and the inner diameter and outer diameter of the protective ring were 54 mm and 64 mm, respectively. The electrode was placed in the center of the sample, a DC voltage of 100 V was applied, and the resistance was read and the surface resistivity was calculated after 60 s. The test principle was in accordance with IEC 62631-3-2:2023.
[0191] (4) The volume resistivity is determined using the upper and lower electrodes with protective rings. The thickness of the sample at the center and four corners is measured and the average value is taken. A DC voltage of 100V is applied and the volume resistance is read after 60s. The volume resistivity is calculated based on the effective area of the electrodes and the thickness of the sample. The test principle is in accordance with IEC 62631-3-1:2023.
[0192] (5) Take another sample adjusted under the same conditions and measure the electrostatic decay time. Charge the sample surface potential to +1000V and -1000V respectively using corona charging method, hold for 30s and then stop charging. Record the time required for the surface potential to decay from +1000V to +100V and from -1000V to -100V. The test principle refers to IEC 61340-2-1:2015.
[0193] (6) Surface resistivity and volume resistivity are expressed as the geometric mean of the test results of 5 samples; electrostatic decay time is expressed as the arithmetic mean ± standard deviation of the test results of 10 positive and negative potentials.
[0194] The test results are shown in Tables 8 and 9.
[0195] Table 8. Initial antistatic performance test results under conditions of 23℃ and 50% relative humidity: ; Table 9. Initial antistatic performance test results under the conditions of 23℃ temperature and 12% relative humidity: ; According to Tables 8 and 9, the surface resistivity of Examples 1–6 under a relative humidity of 50% is 8.43 × 10⁻⁶. 5 ~1.17×10 7 The electrostatic decay time was 0.16–0.78 s. Under a relative humidity of 12%, the surface resistivity and electrostatic decay time increased, but remained at a similar order of magnitude. The conductive filler content in Examples 3 and 5 was higher, and their resistivity was lower than that in other examples; the conductive filler content in Example 2 was lower, and its resistivity was relatively higher.
[0196] Compared to Example 1, Comparative Example 1 added all raw materials at once, and its surface resistivity under relative humidity conditions of 50% and 12% was 4.83 × 10⁻⁶. 7 Ω and 1.94×10 8 The resistivity and electrostatic decay time of both Comparative Example 4 and Comparative Example 5, which did not undergo short-term heating compatibility treatment, were higher than those of Example 1, indicating that the order and conditions of compatibility treatment affect the effective connection between conductive components.
[0197] Comparative Example 9 used a single first conductive carbon black, while Comparative Example 10 added all micron-sized flake graphite during the pre-dispersion stage. Both examples showed higher resistivity under different humidity conditions compared to Example 1. These results indicate that the staged addition of the two types of conductive carbon black and the segmented addition of micron-sized flake graphite correspond to lower initial resistivity and less influence from humidity.
[0198] Comparative Example 3, without intermediate vacuum dehydration, had a surface resistivity that decreased from 1.58 × 10⁻⁶ under 50% relative humidity conditions. 7 Ω increased to 9.66 × 10⁻⁶ under conditions of 12% relative humidity. 7 The humidity variation was higher in Comparative Example 8 than in Example 1. Comparative Example 8, which did not contain UHMWPE micropowder, had initial electrical properties similar to Example 1, indicating that UHMWPE micropowder has a relatively small impact on initial antistatic properties, and its effect is mainly evaluated in conjunction with the electrical properties after wear.
[0199] The above results indicate that controlled humidity conditioning and intermediate dehydration, delayed compatibility of PE-g-MAH, staged addition of two types of conductive carbon black, and staged addition of micron-sized flake graphite correspond to lower initial resistivity, shorter electrostatic decay time, and lower humidity sensitivity.
[0200] Test Example 5: The testing steps are as follows: (1) The masterbatches obtained in Examples 1-6 and Comparative Examples 1-10 were used as test objects. Each group of masterbatches was mixed with HDPE of the same specification at a mass ratio of 20:80, and dried and injection molded according to the conditions of Test Example 4. The Taber abrasion test specimen was 100mm×100mm×2mm in size, with a mounting hole of 6.5mm in diameter in the center; the friction coefficient test specimen was 60mm×60mm×2mm in size. Independent test specimens were prepared for each group before abrasion, after 250 abrasion cycles, after 500 abrasion cycles, and after 1000 abrasion cycles, with 5 test specimens used for each condition.
[0201] (2) The sample was conditioned in an environment of 23℃ and 50% relative humidity for 48h. The mass of the worn sample before wear was weighed using an analytical balance with a resolution of 0.1mg.
[0202] (3) The test was conducted using a dual-wheel Taber abrasion tester. The grinding wheel model was CS-10, the single-wheel load was 500g, and the sample rotation speed was 60r / min. The grinding wheel was dressed 25 times before the test began, and dressed again 25 times after a cumulative wear of 500 times. Loose abrasion debris was continuously removed during the abrasion process. The test principle was in accordance with ISO 9352:2012.
[0203] (4) The sample used for the wear weight loss test was continuously worn for 1000 cycles. After the wear was completed, the surface debris was blown off with oil-free dry air, and the sample was conditioned for 24 hours at 23°C and 50% relative humidity before weighing. The Taber wear weight loss is the difference in mass before and after wear.
[0204] (5) The surface resistivity of the wear track region was measured using parallel conductive rubber electrodes. The effective electrode length L and electrode spacing d were both 8 mm. The electrodes were arranged along the tangent of the wear track. A DC voltage of 100 V was applied, and the surface resistance R was read after 60 s. s And convert it according to the following formula: Surface resistivity ρ s =R s ×L÷d.
[0205] Since both L and d are 8 mm in this test, and the geometric coefficient L÷d is 1, the surface resistivity value is the same as the surface resistance value read by the instrument. Four locations were selected on the wear trajectory for each sample, and the geometric mean was taken.
[0206] (6) The electrostatic decay time of the sample after 1000 wear cycles was determined. The test area was limited to the wear trajectory, and the surface potential was charged to +1000V and -1000V respectively. After holding for 30s, the charging was stopped, and the time required for the potential to decay to +100V and -100V was recorded. Five samples were tested in each group, and the test principle was in accordance with IEC 61340-2-1:2015.
[0207] (7) The dynamic friction coefficient was determined using a ball-disc friction and wear tester. The grinding balls were 6mm diameter GCr15 steel balls, the normal load was 5N, the wear track radius was 10mm, the sliding speed was 0.10m / s, and the total sliding distance was 100m. The data from the first 20m running-in period were discarded, and the average value within the range of 20 to 100m was taken as the dynamic friction coefficient. The testing principle was in accordance with ASTM G99-23.
[0208] (8) Taber wear weight loss and dynamic friction coefficient are expressed as the average value ± standard deviation of 5 samples, and surface resistivity is expressed as the geometric mean of the test results of 5 samples. The increase factor of surface resistivity after 1000 wear cycles is calculated as the ratio of surface resistivity after wear to surface resistivity before wear.
[0209] The test results are shown in Tables 10 to 12.
[0210] Table 10. Test results of Taber wear weight loss and dynamic friction coefficient in the examples and comparative examples: ; Table 11 Surface resistivity test results of the examples and comparative examples under different wear cycles: ; Table 12. Antistatic performance test results of the examples and comparative examples after 1000 wear cycles: ; According to Tables 10-12, the Taber wear weight loss of Examples 1-6 was 14.9-24.6 mg / 1000 cycles, and the dynamic friction coefficient was 0.157-0.209. After 1000 wear cycles, the surface resistivity increased by 1.88-2.89 times, and the electrostatic decay time was 0.28-1.58 s. Examples 3 and 5 had higher amounts of UHMWPE and micron-sized flake graphite, resulting in relatively lower wear weight loss and dynamic friction coefficient.
[0211] Compared to Example 1, Comparative Example 6, which did not undergo cooling after compatibility treatment, showed an increased abrasion weight loss of 37.2 mg / 1000 cycles and a surface resistivity increase factor of 17.76. Comparative Example 7, which included the pre-added UHMWPE micropowder and post-conductive filler, showed an abrasion weight loss of 41.8 mg / 1000 cycles and a surface resistivity increase factor of 34.49. These results indicate that cooling after compatibility treatment and employing post-low-shear mixing corresponds to lower abrasion losses and better post-abrasion electrical properties.
[0212] Comparative Example 8, without the addition of UHMWPE micropowder, had a surface resistivity similar to that of Example 1 before wear, but its wear weight loss increased to 52.7 mg / 1000 cycles, and the surface resistivity increased by a factor of 115.23 after 1000 wear cycles. These results indicate that UHMWPE micropowder has a relatively small effect on the initial resistivity, but is related to wear resistance and conductivity retention after wear.
[0213] Comparative Example 9 used a single type of first conductive carbon black, while Comparative Example 10 added all micron-sized flake graphite during the pre-dispersion stage. The surface resistivity increases by factors of 14.01 and 19.48 after 1000 wear cycles, respectively, both higher than that of Example 1. The staged addition of the two types of conductive carbon black and the segmented addition of the micron-sized flake graphite are beneficial in reducing the decline in conductivity during continuous wear.
[0214] The above results indicate that the combined use of UHMWPE micro powder, two types of conductive carbon black, and micron-sized flake graphite, along with compatibility treatment followed by cooling, post-positioning of wear-resistant conductive components, and low-shear mixing, corresponds to lower wear weight loss, dynamic friction coefficient, and increase in resistivity after wear.
[0215] Test Example 6: The testing steps are as follows: (1) The masterbatches obtained in Examples 1 to 6 and Comparative Examples 1 to 10 were used as test objects. Each group of masterbatches was mixed with HDPE of the same specification at a mass ratio of 20:80, dried at 80°C for 4 hours, and tensile test specimens and notched impact test specimens were prepared according to the injection molding conditions of Test Example 4.
[0216] (2) Type 1A specimens were used for tensile testing and were conditioned for 48 hours at 23°C and 50% relative humidity. The tensile modulus test speed was 1 mm / min, and the tensile strength and elongation at break test speed was 50 mm / min. Five valid specimens were tested in each group, and the testing principles were in accordance with ISO 527-1 and ISO 527-2.
[0217] (3) The notched impact specimen is 80mm×10mm×4mm in size, with an A-type V-shaped notch and a remaining width of 8mm at the notch. After the specimens are adjusted under the same conditions, a 2J pendulum is used to conduct a lateral impact test on a simply supported beam. Ten valid specimens are tested in each group. The test principle is in accordance with ISO 179-1.
[0218] (4) Repeated processing stability test: Example 1, Comparative Example 1, Comparative Example 4, Comparative Example 7 and Comparative Example 9 were selected. Each group of masterbatch was mixed with HDPE of the same specification at a mass ratio of 20:80. 15 kg of each group was prepared and dried at 80°C for 4 h before repeated melt extrusion.
[0219] (5) Repeated processing was performed using the same co-rotating twin-screw extruder with a length-to-diameter ratio of 40:1. The temperature zones from the feed end to the die head were set sequentially to 170℃, 180℃, 190℃, 200℃, 200℃, 195℃, 190℃, and 185℃, with a screw speed of 200 r / min and a feed rate of 10 kg / h. The extrudate was air-cooled and pelletized to obtain primary repeated extrusion pellets. After drying, the pellets were extruded again under the same conditions to obtain secondary and tertiary repeated extrusion pellets. No antioxidants, lubricants, or other additives were added during the repeated processing.
[0220] (6) The granules obtained from the first, second, and third repeated extrusions were dried at 80°C for 4 hours, and the melt flow rate was measured. Electrical properties, tensile strength, and notched impact strength specimens were prepared. Test specimens were prepared from the granules obtained from each repeated extrusion under the same injection molding conditions. The number of repeated extrusions was not counted in the injection molding process. The test conditions for melt flow rate were 190°C, 5.0 kg, and a preheating time of 6 min. Five segments of extrudate were continuously cut from each sample, and the average value and standard deviation were calculated. Surface resistivity and volume resistivity were determined according to the method in Test Example 4. Tensile strength and notched impact strength were determined according to the methods in items (2) and (3) of this Test Example.
[0221] (7) Basic mechanical properties, melt flow rate, tensile strength and notched impact strength are expressed as mean ± standard deviation; surface resistivity and volume resistivity are expressed as geometric mean.
[0222] The test results are shown in Tables 13 to 15.
[0223] Table 13. Basic mechanical property test results of the examples and comparative examples: ; Table 14. Test results of melt flow and electrical properties under different repeated extrusion cycles: ; Table 15. Mechanical property test results under different repeated extrusion cycles: ; According to Table 13, the tensile strength of Examples 1–6 is 24.2–27.3 MPa, the elongation at break is 228%–389%, and the notched impact strength is 23.6–32.4 kJ / m. 2 Examples 3 and 5 have higher conductive filler content, resulting in relatively higher tensile modulus, but relatively lower elongation at break and notched impact strength; Example 2 has lower conductive filler content, resulting in relatively higher toughness.
[0224] Compared to Example 1, Comparative Example 1 added all raw materials at once, and Comparative Example 4 added PE-g-MAH in advance. Both showed reduced tensile strength, elongation at break, and notched impact strength. Comparative Example 6 did not undergo cooling after compatibility treatment, and Comparative Example 7 added UHMWPE micropowder and post-conductive filler in advance; its notched impact strength was 18.7 kJ / m. 2 and 17.4 kJ / m 2 The results show that the phased feeding, delayed compatibility, and post-low shear mixing maintain the corresponding mechanical properties.
[0225] Comparative Example 8, without the addition of UHMWPE micropowder, exhibited tensile strength similar to that of Example 1, but lower elongation at break and notched impact strength. Combined with the abrasion test results, the UHMWPE micropowder had a relatively small impact on tensile strength, but its effect was related to the material's toughness and abrasion resistance.
[0226] According to Tables 14 and 15, with the increase of the number of repeated extrusions, the melt flow rate and resistivity of each group of materials increased, while the tensile strength and notched impact strength decreased accordingly. The surface resistivity of Example 1 after three repeated extrusions was 5.73 × 10⁻⁶. 6 Ω is 1.77 times that after one repeated extrusion; tensile strength and notched impact strength remain at 95.7% and 91.4% of the values after one repeated extrusion, respectively.
[0227] The surface resistivity of Comparative Examples 1, 4, and 7 after three repeated extrusions was 4.55 times, 4.23 times, and 6.63 times that after one repeated extrusion, respectively, and the notched impact strength retention rates were 72.9%, 77.1%, and 62.7%, respectively. Comparative Example 9, using a single primary conductive carbon black, had a surface resistivity of 5.31 times that after one repeated extrusion after three repeated extrusions, and a notched impact strength retention rate of 79.9%.
[0228] The above results indicate that controlled humidity conditioning and intermediate dehydration, delayed compatibility of PE-g-MAH, cooling after compatibility treatment, and post-treatment low-shear addition of the wear-resistant conductive component correspond to the maintenance of basic mechanical properties and stability during repeated processing. In Example 1, after three melt extrusions, the electrical properties remained within a similar order of magnitude, while the decrease in mechanical properties was relatively small.
[0229] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. An antistatic and wear-resistant modified HDPE plastic masterbatch, characterized in that, The masterbatch is made from raw materials comprising the following parts by weight: 35-55 parts of high-density polyethylene; 12-17 parts of ethylene-vinyl alcohol copolymer; 12-18 parts of first conductive carbon black; 2-6 parts of second conductive carbon black; 5-9 parts of micron-sized flake graphite; 8-12 parts of ultra-high molecular weight polyethylene micro powder; 4-7 parts of maleic anhydride-grafted polyethylene; Oxidized polyethylene wax 0.5 to 2 parts; 0.4 to 1 part of compound antioxidant; 0.3 to 0.8 parts of calcium stearate.
2. The antistatic and wear-resistant HDPE modified plastic masterbatch according to claim 1, characterized in that, The first conductive carbon black has an oil absorption value of 250–420 mL / 100 g and a BET specific surface area of 500–1400 m². 2 / g; the second conductive carbon black has an oil absorption value of 120-220 mL / 100g and a BET specific surface area of 60-500 m² / g. 2 / g; the oil absorption value of the first conductive carbon black is at least 60mL / 100g higher than that of the second conductive carbon black, and the volatile matter content of the first conductive carbon black is at least 0.50 percentage points higher than that of the second conductive carbon black.
3. The antistatic and wear-resistant HDPE modified plastic masterbatch according to claim 1, characterized in that, The viscosity-average molecular weight of the ultra-high molecular weight polyethylene micropowder is 2.0 × 10⁻⁶. 6 ~6.0×10 6 g / mol, D50 is 20-60 μm, D90 is not higher than 120 μm; the ethylene-vinyl alcohol copolymer has an ethylene structural unit content of 38-44 mol.
4. The antistatic and wear-resistant HDPE modified plastic masterbatch according to claim 1, characterized in that, The micron-sized flake graphite includes a first part of micron-sized flake graphite and a second part of micron-sized flake graphite, wherein the weight ratio of the first part of micron-sized flake graphite to the second part of micron-sized flake graphite is 1:1 to 1:
2. The first portion of micron-sized flake graphite is used to prepare EVOH-based conductive predispersant with ethylene-vinyl alcohol copolymer, first conductive carbon black, oxidized polyethylene wax and a portion of high-density polyethylene; the second portion of micron-sized flake graphite is used to form a post-mixture with ultra-high molecular weight polyethylene powder, second conductive carbon black and calcium stearate.
5. The antistatic and wear-resistant HDPE modified plastic masterbatch according to claim 1, characterized in that, The raw materials, on an oven-dry basis, are expressed in the following parts by weight: 40-45 parts of high-density polyethylene; 13-15.5 parts of ethylene-vinyl alcohol copolymer; First conductive carbon black 13.5–16.5 parts; 3.4 to 4.5 parts of the second conductive carbon black; 6.5–7.5 parts of micron-sized flake graphite; 9-10.5 parts of ultra-high molecular weight polyethylene micro powder; 5-6 parts of maleic anhydride-grafted polyethylene; 1 to 1.5 parts of oxidized polyethylene wax; 0.5–0.7 parts of compound antioxidant; 0.5 to 0.6 parts of calcium stearate.
6. A preparation process for the antistatic and wear-resistant HDPE modified plastic masterbatch as described in any one of claims 1-5, characterized in that, Includes the following steps: Step 1: The ethylene-vinyl alcohol copolymer, which has been moistened with deionized water, is melt-blended with the first conductive carbon black, the first part of micron flake graphite, oxidized polyethylene wax and part of high-density polyethylene in the first extrusion stage. Then, it is subjected to vacuum dehydration, extrusion and pelletizing to obtain EVOH-based conductive predispersant. Step 2: The EVOH-based conductive pre-dispersed material, the remaining high-density polyethylene and composite antioxidant are added to the extruder for PE-g-MAH pre-mixing. After venting through the first vacuum exhaust port and establishing a melt seal, maleic anhydride grafted polyethylene is added through the side feed port for heating and compatibility treatment to obtain the compatibility-treated melt. Step 3: Cool the melt obtained in Step 2, and then add a post-addition mixture consisting of ultra-high molecular weight polyethylene micro powder, second conductive carbon black, second part of micron flake graphite and calcium stearate through the side feed port. Mix in the low shear mixing section, vent through the second vacuum exhaust port, extrude, cool and pelletize to obtain the antistatic and wear-resistant HDPE modified plastic masterbatch.
7. The preparation process according to claim 6, characterized in that, In step one, the ethylene-vinyl alcohol copolymer is pre-treated to adjust its moisture content: The ethylene-vinyl alcohol copolymer was dried at 80°C to reduce its moisture content to no more than 0.10%. Then, it was stirred in a closed mixer at 25°C and deionized water was sprayed in evenly. The mixture was then left to stand in a sealed container for 6 to 10 hours to adjust the moisture content of the ethylene-vinyl alcohol copolymer to 0.3% to 0.8%. The amount of deionized water used was 0.03 to 0.15 parts by weight.
8. The preparation process according to claim 6, characterized in that, In step one, the first extrusion stage is carried out using a co-rotating twin-screw extruder with a length-to-diameter ratio of 44:1; the process parameters for vacuum dehydration are: the vacuum gauge pressure of the vacuum dehydration section is -0.095 to -0.085 MPa, and the temperature of the vacuum dehydration section is 185 to 192°C, so that the moisture content of the dehydrated EVOH-based conductive pre-dispersed material is not higher than 0.10%.
9. The preparation process according to claim 6, characterized in that, In step two, the heating and compatibility treatment is carried out in the compatibility treatment section, where the melt temperature is 198-208°C and the average residence time of the material in the compatibility treatment section is 8-20 seconds. Maleic anhydride-grafted polyethylene is added through the side feed port 32D downstream of the main feed port, where D represents the nominal diameter of the screw of the twin-screw extruder.
10. The preparation process according to claim 6, characterized in that, In step three, before adding the post-addition mixture, the melt is passed through a cooling conveying section to reduce the melt temperature to 178-182°C. After adding the post-addition mixture, low-shear mixing is carried out at 178-182°C, and the average residence time of the material is 20-45 seconds. The low-shear mixing section uses forward conveying elements and 30° kneading elements, and does not have reverse conveying elements.
